Vaccine hesitancy and related factors among South African adults in 2021: unpacking uncertainty versus unwillingness - Sewpaul, Ronel; Sifunda, Sibusiso; Gaida, Razia; Mokhele, Tholang; Naidoo, Inbarani; Reddy, Sasiragha Priscilla (Frontiers in Public Health, 2023)
Background: Amidst widespread public health recommendations and availability of COVID-19 vaccinations, half of South African adults are vaccinated against COVID-19. This study investigated the socio-behavioural determinants of vaccine hesitancy in South Africa, where vaccine hesitancy was separated into unwilling ness and uncertainty to take a COVID-19 vaccine.Methods: Data was collected from a large-scale public survey during June-October 2021 that included online and telephonic surveys. Vaccination hesitancy was based on the question "When available, would you take the COVID 19 vaccine?", with responses categorised into those who were willing, unwilling, and uncertain about taking a COVID-19 vaccine. Multinomial regression examined the association between socio-behavioural variables and vaccine hesitancy.Results: Overall, 73.8% reported they would definitely or probably take the vaccine, 16.4% were uncertain and 9.9% reported they probably or definitely would not (n=16,988). Younger age, White and Coloured population groups, no influenza vaccination history, previous vaccination refusal, knowing someone who experienced a serious vaccination side-effect, misperceptions about vaccine benefits, cultural or religious discouragement from taking a COVID-19 vaccination, lack of governmental confidence, concerns about side-effects, perceived lack of safety information, and lack of trust in the pharmaceutical industry and in the information from health care providers were all associated with higher odds of being uncertain and unwilling to take a COVID-19 vaccination. Strengths of association for unwillingness and uncertainty varied by the explanatory variables. Concern about effectiveness due to fast development was associated with uncertainty to take the vaccine but not with unwillingness. Concerns about side-3 effects had stronger associations with uncertainty than with unwillingness, while previous vaccine refusal, misperceptions of the protective benefits of vaccines, White population group, religious/cultural discouragement, and lack of trust in the pharmaceutical industry and health care providers' information had stronger associations with unwillingness than uncertainty.: The determinants of COVID-19 vaccine hesitancy should be addressed in interventions to improve vaccine uptake. Public health interventions and health communication can be prioritised and tailored to the different forms of vaccination hesitancy.